Analysis of Contract Change Order (CCO) in the Samarinda Road Preservation Project - Devedo, Mochamad Gaharu; Lestari, Dyah Ayu (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2025)
Road infrastructure improvement is crucial for supporting economic growth and urban development, particularly in cities like Samarinda, East Kalimantan, which faces challenges due to increasing traffic volumes. To address this, the Public Works Department initiated a road preservation project aimed at enhancing the city’s road network. However, unforeseen changes during execution, known as contract change orders (CCOs), are common in construction projects and can affect costs, timelines, and quality. CCOs often arise from fluctuating material prices, design revisions, or external factors. Effective management, including risk analysis and clear communication, is crucial for minimizing delays and cost overruns. This study examines CCOs in a road preservation project in Samarinda, focusing on their causes, impacts, and management strategies. Data collection includes primary data from the contractor’s project monitoring documents and secondary data from literature studies. Quantitative analysis is used to assess the causes and impacts of CCOs, measured by Change Order Ratio (COR) and Change Order Ratio in Addition (CORA). The research aims to identify key factors driving contract changes and analyze their effects on cost, time, and quality. For the Samarinda project, COR and CORA were both 2.54%. The contract value increased from Rp1,950,519,068.00 to Rp2,000,079,068.00 due to additional work, with a cost deviation of Rp49,560,000. Despite these changes, the cost deviation was minimal, indicating effective management of contract changes. This study emphasizes the importance of continued evaluation to minimize future changes and ensure the efficiency of road infrastructure projects.